STRATEGI KOMUNIKASI PEMASARAN WOW CATERING PEKANBARU DALAM MEMBANGUN BRAND IMAGE - MARLIANA RAMADANI A; Nova Yohana YOHANA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
One catering competent in Pekanbaru the WOW Catering. Catering is a company engaged in the field of catering services, which stood since 15 March 2008. Catering is experienced in the fields of food, beverages, as well as the manner of presentation and trusted to handle the companies which is quite famous in this Pekanbaru. With the cooperation already established relationships result in satisfaction for both in terms of food, beverage, which is rich in variations, full of flavor and most importantly meet health standards. In the past, many people hesitate to wear catering because of the lack of health standards of ISO (International Organization for Standardization). As with the now consumers have trusted catering because of the health standards that have been owned by a business engaged in catering ini.Tujuan this study was to menetahui strtategi marketing communications in building brand image through advertising, sales promotion, publicity and public relations , personal selling and direct marketing. This study used qualitative methods .Penelitian is done in the company Wow Catering pekanbaru housed in the Mangga 15 Pekanbaru. This study used a technique purposive.Tekhnik data collection by interview, observation, dokumentasi.Informan on this research that there is one person Marketing Executive, Customer 8 Wow Catering, 2 prospective customers and 1 Relation Wow Wow Catering Catering Pekanbaru. These results indicate that marketing communications strategies Wow Catering pekanbaru in building brand image through activities Advertising using social media Facebook, brochures and flyers. Sales promotion activities for promo menus and discounts. Personal selling activities do live presentations, invited presentations and go make a presentation. Direct marketing activities carried out by using a tool that is E mail and also Telepone.Terakhir, activities carried out on the publicity by publishing the logo Wow Wow Catering Catering through the cars scattered in Pekanbaru city areas while the public relations activities to socialize directly with customers, prospective customers and relationships Wow Catering Pekanbaru.Key words: Marketing Communications Strategy, Brand Image, Promotion Mix